Mediasi dan Pengaruh Switching Cost terhadap Loyalitas Pelanggan - Astini, Rina (Journal the Winners: Economics, Business, Management, and Information System Journal, 2008)
Article presents a measurement of the effects of satisfaction and trust in connection with customer loyalty, and a direct and indirect effects of switching cost on customer loyalty. Data were collected from 42 respondents coming from GSM customers. Data was analyzed by using path analysis methods. The study found that satisfaction did not necessarily affect customers’ loyalty. Relationship of customer satisfaction and trust was greatly influenced by perception of customers towards the cost of switching. Level of satisfaction and respondent loyalty average was 69.7% and the average value of customer loyalty was 78.73%. The research result indicates that trust and switching cost jointly influence customer loyalty. Trust is more important than customer satisfaction in influencing customer loyalty, where the trust contains belief towards a brand, which will produce a positive outcome both in the present and in the future. Customer satisfaction does not contain this dimension. It is concluded that GSM operators shall have to focus on trust rather than satisfaction.